Estimación del indicador de calidad de vida para el departamento de Antioquia (2010)
ABSTRACT: This paper presents the estimation of the Indicator of Quality of Life (ICV) for the homes of the department of Antioch. The used statistical methodology is based on the use of the methods of Quantification of Qualitative Variables and the Analysis Nonlinear of Main Components. A description of this methodology is in Young (1981), Gifi (1990) and one brief introduction is in the Appendix. Based on the information provided by the Survey of Quality of realised Life year 2007, indicators were constructed to as much measure the quality of life of the homes in the urban sector as rural. These indicators are a summary of different characteristics related to the house, demographic aspects of the people who compose the home, the access to the services public, and the human capital and the social security of the home. The indicator assigns to each home a puntaje varies between zero and one hundred: As the value of the index increases, the conditions of life of the home improve. The objective of this document is to analyze, based on the new Survey of Quality of Life realised in 2009, the evolution of the urban and rural conditions of life of the department with respect to the found ones in 2007 and for determining if they are changing significantly.